2010
DOI: 10.1007/s10333-010-0203-9
|View full text |Cite|
|
Sign up to set email alerts
|

Safe application of reclaimed water reuse for agriculture in Korea

Abstract: This article describes the pilot study on the water reuse for agricultural irrigation in Korea. The project is a part of the application of wastewater reuse system for Agriculture project, a 21st Century Frontier R&D Program sponsored by the Ministry of Education, Science, and Technology and associated with the Sustainable Water Resources Research Program. The goal of the project was to develop infra-technologies necessary to reclaim wastewater for irrigation in agriculture. The project involved two phases: la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…It was also found that the total coliform of the irrigation water containing untreated wastewater was about 77,000 MPN/100 mL [21]. QMRA on paddy irrigation showed that the human health risk of irrigating treated wastewater is nine times higher than that of irrigating groundwater [42], but even with the extremely high level of total coliform, there have rarely been any reports of human harm from using treated or untreated wastewater for rice paddy irrigation. This indicates that the subjected level of total coliform can be easily found in nature and is inadequate as an indicator for microbes.…”
Section: Coliform Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the total coliform of the irrigation water containing untreated wastewater was about 77,000 MPN/100 mL [21]. QMRA on paddy irrigation showed that the human health risk of irrigating treated wastewater is nine times higher than that of irrigating groundwater [42], but even with the extremely high level of total coliform, there have rarely been any reports of human harm from using treated or untreated wastewater for rice paddy irrigation. This indicates that the subjected level of total coliform can be easily found in nature and is inadequate as an indicator for microbes.…”
Section: Coliform Bacteriamentioning
confidence: 99%
“…They have also focused on the upland irrigation including vegetables and have not well considered the characteristics of irrigation water in paddy fields: Irrigation water for paddy rice production accounts for more than 70% of the total irrigation water in Asia [40], and paddy rice is the largest consumer of freshwater resources in South and Southeast Asia [41,42]. This study, therefore, examines existing water quality criteria for irrigation water and wastewater reuse, and analyzes the water quality standards of other countries to set agricultural water quality standards for indirect wastewater reuse considering both paddy and upland irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, farm conditions for wastewater reuse are directly associated with the health condition of the farmer and consumer (Jang et al , ). WHO () suggested the target water quality based on crop types and irrigation methods.…”
Section: Classification Of Wastewater Reusementioning
confidence: 99%
“…Reclaimed wastewater in agriculture has been considered an important alternative irrigation water resource in a growing water demand and freshwater shortage situation (Raschid‐Sally et al , ; Jang et al , ; Chang and Ma, ). Wastewater is used as irrigation on more than 20 million ha of agricultural land throughout the world, and food products from farmland irrigated with wastewater are consumed by more than 10% of the world's population (World Health Organization (WHO), ; Hamilton et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation